MENINGKATKAN HASIL BELAJAR GEOGRAFI PADA MATERI LINGKUNGAN HIDUP DENGAN MENGGUNAKAN PEMBELAJARAN JIGSAW DI KELAS XI IPS 1 SMAN 1 ANGKINANG TAHUN AJARAN 2013/2014 - Ervina Royani (Universitas Lambung Mangkurat, 2014)
As one of the reasons this research is the initial observations of student learning outcomes in Geography subjects at XI IPS 1 SMAN 1 Angkinang were low. Indeed, to make innovation in learning model teacher should improve learning outcomes of Geography. This study aims to improve student learning out comes by applying the Jigsaw learning model. This research is aclassroom action research consist of two cycles, each cycle consisting of one meeting. This research was conducted at SMAN1 Angkinang by subjects the students of grade XI IPS 1 the number of 21 students in the school year 2013/2014. The result shows that learning out comes at the first cycle is post-test average 80.57 and 85.71% in classical completeness, the post-test average 91.3 and 100% classical completeness at the second cycle. Response of students in dicated a positive responset the use of jigsaw learning model. It can be seen from the student’s responses were expressed strongly agreed 33.33% -95.24%, agree 4.76% -52.38%, disagree 4.76% -23.80%, and thestrongly disagree 4.76% -14.28%. Based on the findings in this researchis recommended for teachers and other researchers to use the Jigsaw model in teaching and learning process.Keywords: Jigsaw model of learning, learning outcomes of Geography